Pelayanan Administrasi Kependudukan di Kelurahan Genteng Kota Surabaya pada Pelayanan Kartu Keluarga dan Akta Kelahiran - Nur Firdaus, Lailatul (Policy, Law and Political Research Center, 2023)
The Population Administration Service focuses on providing Family Cards and Birth Certificates, which are universal, lifelong documents issued by authorized officials by recording a person's data. The family card contains data about the composition, relationship and number of family members. At the same time, birth certificates play an important role in proving legal certainty of personal identity and as a state basis to guide government budgeting policies (both at the central and regional levels). The provision of population administration services provided to the community can be fulfilled and satisfied, and provides a good service focus. Good service expects service providers, customers or stakeholders from service activities to have references about the form, reason, time, place, and process of service being carried out. The type of research in this article is descriptive qualitative. This study uses analytical methods, namely exploratory research, interviews, and data collection. The results of this study focus on six indicators, namely Service Policy, Professionalism of Human Resources (HR), Public Service Infrastructure, Public Service Information Systems, Complaint Consultation, and Innovation.